Analisis Kesiapan Siswi Sekolah Dasar dalam Menghadapi Menarche - Indah Lutfiya (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
Puberty among female adolescent occurred when coming to menarche period. The age of menarche among girls in Indonesia has decreased in recent years. It impacts on readiness of menarche among pre puberty female adolescent, both physically and mentally. There were many girls who stated that they didn’t ready to face menarche. The unreadiness of female adolescent on experience menarche will impact to their behavior of vulva hygiene and increase the risk of being infected by sexually transmitted diseases. Surabaya is one of the cities in East Java province which the highest number of female adolescents. SDN (State Elementary School) Pacarkembang 1/192, Tambaksari District of Surabaya contributed to the most number of pre puberty female adolescent in Surabaya. The purpose of this research was to analyze factor that aff ect readiness of menarche among pre puberty female adolescent. Variable on this study covered parenting style, knowledge of female adolescent and number of source information. This research was an analytical research with observational method. The population in this study were Elementary Student who in grade four and fi ve with sample number of 55 students. This study used random sampling. Analysis of data used logistic regression. The result shown that variable of knowledge eff ecting significantly (p = 0.012; PR = 6.000). Female adolescent who has better knowledge would be more ready to face menarche. This study suggested to maximize the role of school and student parents’ association to improve reproductive health knowledge program.